2021
DOI: 10.1542/peds.2020-023549
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis Risk in Transgender Adolescents Receiving Gender-Affirming Hormone Therapy

Abstract: BACKGROUND AND OBJECTIVES: Many transgender youth experience gender dysphoria, a risk factor for suicide. Gender-affirming hormone therapy (GAHT) ameliorates this risk but may increase the risk for thrombosis, as seen from studies in adults. The aim with this study was to examine thrombosis and thrombosis risk factors among an exclusively adolescent and young adult transgender population. METHODS: This retrospective chart rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 34 publications
0
33
0
5
Order By: Relevance
“…There is strong evidence demonstrating the benefits in quality of life and well-being of gender-affirming treatments, including endocrine and surgical procedures, properly indicated and performed as outlined by the Standards of Care (Version 8), in TGD people in need of these treatments (e.g., Ainsworth & Spiegel, 2010 ; Aires et al., 2020 ; Aldridge et al., 2020 ; Almazan & Keuroghlian, 2021 ; Al-Tamimi et al., 2019 ; Balakrishnan et al., 2020 ; Baker et al., 2021 ; Buncamper et al., 2016 ; Cardoso da Silva et al., 2016 ; Eftekhar Ardebili, 2020 ; Javier et al., 2022 ; Lindqvist et al., 2017 ; Mullins et al., 2021 ; Nobili et al., 2018 ; Owen-Smith et al., 2018 ; Özkan et al., 2018 ; T’Sjoen et al., 2019 ; van de Grift, Elaut et al., 2018 ; White Hughto & Reisner, Poteat et al., 2016 ; Wierckx, van Caenegem et al., 2014 ; Yang, Zhao et al., 2016 ). Gender-affirming interventions may also include hair removal/transplant procedures, voice therapy/surgery, counseling, and other medical procedures required to effectively affirm an individual’s gender identity and reduce gender incongruence and dysphoria.…”
Section: Chapter 2 Global Applicabilitymentioning
confidence: 99%
“…There is strong evidence demonstrating the benefits in quality of life and well-being of gender-affirming treatments, including endocrine and surgical procedures, properly indicated and performed as outlined by the Standards of Care (Version 8), in TGD people in need of these treatments (e.g., Ainsworth & Spiegel, 2010 ; Aires et al., 2020 ; Aldridge et al., 2020 ; Almazan & Keuroghlian, 2021 ; Al-Tamimi et al., 2019 ; Balakrishnan et al., 2020 ; Baker et al., 2021 ; Buncamper et al., 2016 ; Cardoso da Silva et al., 2016 ; Eftekhar Ardebili, 2020 ; Javier et al., 2022 ; Lindqvist et al., 2017 ; Mullins et al., 2021 ; Nobili et al., 2018 ; Owen-Smith et al., 2018 ; Özkan et al., 2018 ; T’Sjoen et al., 2019 ; van de Grift, Elaut et al., 2018 ; White Hughto & Reisner, Poteat et al., 2016 ; Wierckx, van Caenegem et al., 2014 ; Yang, Zhao et al., 2016 ). Gender-affirming interventions may also include hair removal/transplant procedures, voice therapy/surgery, counseling, and other medical procedures required to effectively affirm an individual’s gender identity and reduce gender incongruence and dysphoria.…”
Section: Chapter 2 Global Applicabilitymentioning
confidence: 99%
“…811 papers were excluded as irrelevant, based on title and abstract reading. Hence, as shown in Figure 1, 99 studies were identified, of which 18 met the inclusion criteria (17,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49). The studies by Asscheman and colleagues published in 1989 (50) and 2011 (51) were excluded since the population under investigation was already included in the paper by van Kesteren et al, 1997 (47).…”
Section: Study Selection and Quality Assessmentmentioning
confidence: 99%
“…The data regarding testosterone and VTE risk in the TGD population is mainly derived from adult subjects and lacks robust evidence from the adolescent population. A recent retrospective cohort study showed no cases of VTE among TGD adolescents on testosterone therapy in one clinical setting 20. Overall, conclusions from the literature regarding testosterone therapy have been conflicting, and case reports for the adolescent TGD population may suggest an association of testosterone and VTE 21–23.…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective cohort study showed no cases of VTE among TGD adolescents on testosterone therapy in one clinical setting. 20 Overall, conclusions from the literature regarding testosterone therapy have been conflicting, and case reports for the adolescent TGD population may suggest an association of testosterone and VTE. [21][22][23] Among adolescents, one case report describes a 17-year-old transgender male receiving masculinizing therapy for male gender affirmation who presented with bilateral pulmonary emboli.…”
Section: Discussionmentioning
confidence: 99%